Acute beetroot juice supplementation enhances judo-specific performance, explosive power, and muscular strength in recreational adolescent judokas: a randomized crossover trial - Demirli, Abdullah; Gökçelik, Eda; Moghanlou, Abdorreza Eghbal; Ocak, Muhammed Hüseyin; Terzi, Merve; Yamaner, Emre; Atıcı, Müjde; Akyüz, Ömer; Toy, Ali Burak (Frontiers in Nutrition, 2025)
ObjectiveDietary supplementation with beetroot juice (BRJ), rich in nitrate, enhances nitric oxide bioavailability and may positively influence exercise performance. However, the impact of acute BRJ ingestion on judo-specific performance has not been investigated. The aim of this study was to determine the acute effects of BRJ on judo-specific performance, explosive power, back-muscle strength, and handgrip strength in recreational adolescent judokas.MethodsThirty-five male adolescent recreational judokas completed a randomized, double-blind, placebo-controlled crossover trial, consuming either 140 mL of BRJ (∼12.8 mmol nitrate) or a placebo, with a 7-day wash-out. In each session, after a 4-min randori, athletes performed the Sargent jump test, back-strength dynamometer pulls, handgrip dynamometer trials, and the Special Judo Fitness Test (SJFT), with a 10-s rest between each performance.ResultsCompared to placebo, BRJ significantly increased explosive jump height (+3%, p < 0.05), back-muscle strength, (+3.2%, p < 0.01), handgrip strength (+8.4%, p < 0.01), and total SJFT throws (+2.4%, p < 0.05), while reducing 1-min post-SJFT heart rate (−7.9 b·min−1, p < 0.001) and improving the SJFT index (−4%, p < 0.001). Immediate post-SJFT heart rate and perceived exertion did not differ between conditions (p > 0.05).ConclusionAcute BRJ is a practical, natural ergogenic aid for adolescent judokas, enhancing explosive power, muscular strength, and judo-specific performance. These findings support the use of nitrate supplementation as an ergogenic aid for young athletes engaged in high-intensity, intermittent exercise activities.